The development of design specification for ergonomics sofa in Malaysia - Khairul Azhar Mat Daud; Ahmad Rasdan Ismail; Suriatini Ismail; Nik Zulkarnaen Khidzir (2016)
To design and develop a sofa that has ergonomic features, designers should identify the features are need to design sofa. To knowing and understanding the appropriate design which concurrent with market demand, the designers must to conduct market survey among users whose are need and use sofa. The desires of users to have a sofa that has the characteristics of safety and health should be examined from a variety of factors. The draft and sketching sofa with an attractive design and meet customer requirements, design specifications need to be developed first. This paper will explain how to develop sofa’s design specifications which have ergonomic features for users in Malaysia. Market survey was organized among three main groups of sofa’s user that is sofa users, sofa makers and sofa retailer.